2006
DOI: 10.1530/rep.1.00617
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine control of reproductive aging: roles of GnRH neurons

Abstract: The process of reproductive senescence in many female mammals, including humans, is characterized by a gradual transition from regular reproductive cycles to irregular cycles to eventual acyclicity, and ultimately a loss of fertility. In the present review, the role of the hypothalamic gonadotropin-releasing hormone (GnRH) neurons is considered in this context. GnRH neurons provide the primary driving force upon the other levels of the reproductive axis. With respect to aging, GnRH cells undergo changes in bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 93 publications
0
57
0
1
Order By: Relevance
“…GnRH cell numbers do not change appreciably with aging so this is probably not the causal event for these alterations documented above (for review, see Yin and Gore, 2006). Rather, inputs to GnRH neurons from other neurotransmitters and glia in the CNS appear to be very important in causing age-associated changes in GnRH output (Gore, 2004).…”
Section: The Circuitry Driving Gnrh Neurons Undergoes Age-related Chamentioning
confidence: 98%
See 3 more Smart Citations
“…GnRH cell numbers do not change appreciably with aging so this is probably not the causal event for these alterations documented above (for review, see Yin and Gore, 2006). Rather, inputs to GnRH neurons from other neurotransmitters and glia in the CNS appear to be very important in causing age-associated changes in GnRH output (Gore, 2004).…”
Section: The Circuitry Driving Gnrh Neurons Undergoes Age-related Chamentioning
confidence: 98%
“…The early menopause transition is associated with lower ovarian inhibin secretion, which in turn reduces the restraint on both the hypothalamus and pituitary and results in elevated pituitary gonadotropin [folliclestimulating hormone (FSH)] secretion. In addition to reduced ovarian inhibin secretion, age-related increases in gonadotropinreleasing hormone (GnRH) production could contribute to the elevated pituitary gonadotropin levels (Maffucci and Gore, 2006;Yin and Gore, 2006). Importantly, ovarian estradiol secretion is normal or at times elevated during this early stage of the menopause transition (Santoro, 2005).…”
Section: Characteristics Of the Menopause Transition: A State Of Consmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that, as aging progresses, gonadotropin levels decrease, as do gonadotropin pulse frequency and amplitude. As a matter of fact, early postmenopausal women (45-55 years) have significantly higher gonadotropin levels compared to late postmenopausal women (70-80 years) [22]. Moreover, there is also evidence that GnRH neurons undergo age-related impairment in terms of biosynthesis, processing, and release of the GnRH decapeptide before reproductive failure, suggesting a contributory role of GnRH cells to reproductive failure itself [23].…”
Section: Discussionmentioning
confidence: 99%